Biomarkers in Vestibular Schwannoma–Associated Hearing Loss - Lassaletta, Luis; Calvino, Miryam; Morales-Puebla, Jose Manuel; Lapunzina, Pablo; Rodriguez-de la Rosa, Lourdes; Varela-Nieto, Isabel; Martinez-Glez, Victor (Frontiers in Neurology, 2019)
Vestibular schwannomas (VS) are benign tumors composed of differentiated neoplastic Schwann cells. They can be classified into two groups: sporadic VS, and those associated to neurofibromatosis type2 (NF2). VSs usually grow slowly, initially causing unilateral sensorineural hearing loss (HL) and tinnitus. These tumors cause HL both due to compression of the auditory nerve and to the secretion of different substances potentially toxic to the inner ear or the cochlear nerve. As more patients are diagnosed and need to be managed, we are more than ever in demand of searching biomarkers associated with these tumors. Owing to an unknown toxic substance generated by the tumor, HL in VS may be linked to high protein amount of perilymph. Previous studies have identified perilymph proteins correlated to tumor-associated HL, including CRYM, LRP2, Ig  4-chain C region, Ig -chain C region, Complement C3, and immunoglobulin heavy constant  3. Besides, the presence of specific subtypes of Heat Shock Protein70 has been suggested to be associated with preservation of residual hearing. It has been recently demonstrated that CXCR4 is overexpressed in sporadic VS as well as in NF2 tumors, and that hearing disability and CXCR4 expression may be correlated. Further, the genetic profile of VS and its relationship with poor hearing has also been studied, including DNA methylation, deregulated genes, growth factors and NF2 gene mutations. The knowledge of biomarkers associated with VS would be of significant value to maximize outcomes of hearing preservation in these patients.